Integrasi Nilai-Nilai Pendidikan Islam dalam Sistem Pendidikan Nasional: Analisis Kebijakan dan Implementasinya di MTs Al-Inayah Kota Cilegon - Hodiqotul Atfaliyah; Wasehudin (Islamic Education Management Study Program, Faculty of Tarbiyah, Sunan Drajat Islamic Boarding School Institute, Lamongan, East Java, Indonesia., 2026)
This study aims to analyze the integration of Islamic educational values within the national education system in Indonesia, both from a policy perspective and its implementation at the educational unit level. This integration is crucial for strengthening student character development, particularly religious, moral, and social values, amidst the dynamics of global change and the development of the digital era. This study employed a qualitative approach with literature review and limited case studies. Data were obtained through analysis of educational policy documents, such as the national curriculum, as well as observations and interviews with educational stakeholders. Data analysis was conducted descriptively and critically, examining the alignment between policy and practice in the field. The results indicate that normatively, the integration of Islamic educational values has been accommodated within the national education system through various regulations and policies, including the strengthening of character education and the implementation of the Independent Curriculum. Values such as faith, piety, honesty, discipline, and responsibility have become part of the national education goals. However, at the implementation level, several obstacles remain, including limited teacher competency, suboptimal integrative learning strategies, and challenges in utilizing digital technology in alignment with religious values. Therefore, a more systematic, contextual, and adaptive integration model is needed to adapt to current developments and increase the effectiveness of implementing character education based on Islamic values in Indonesia.